Valuing ecosystems : a methodological applying approach - Mendes, Isabel (2010)
In this paper the ecosystem's valuation framework is described and discussed at a conceptual and formal level. Following utilitarianism and the capital asset analogy, one defines the concept of ecosystem value and how to quantify it by using individual preference based techniques rooted in welfare economics, namely stated individual preference techniques like Contingent Valuation. Several controversial questions arise when one tries to compute ecosystem's value by using utilitarianism and the capital asset analogy due to the particular ecosystem's natural specifics and the limitations of the economic theoretical framework. These controversial questions are enumerated, analysed, and the most commonly practitioner practices used to overcome the theoretical and technical difficulties of the appliance are assessed.